Ablative Pyrolysis of Beetle-killed Trees - Luo, Guanqun (My University, 2016)
The bark beetle outbreak has severely affected the forests across the western U.S., and the infested trees need to be disposed of to avoid falling and minimize wildfire hazards. Thus, we propose to use ablative pyrolysis to convert beetle-killed wood chips into bio-oil near the harvesting point, greatly reducing the costs of drying, grinding, and transportation. Firstly, we evaluated the effect of degradation stages of beetle-killed trees on the performance of fast pyrolysis using Py-GC/MS, which has not been reported previously. Our results revealed that bio-oil produced from trees that have been attacked and dead for 4 years had similar yield and selectivity to that from the healthy trees. Moreover, oxygenated pyrolysis vapors from beetle-killed trees were upgraded into value-added aromatic hydrocarbons in the presence of HZSM-5 catalyst. According to the contact method between the catalyst and pyrolysis vapors, the catalytic upgrading can be classified into in-situ and ex-situ configurations. In this research, a direct comparison between these methods was made using Py-GC/MS under identical conditions. The in-situ and ex-situ upgrading showed largely similar yields of aromatic volatiles (21-25%) and carbonaceous residues (34-40%), with differences primarily on species selectivity. As a result of the alkylation/dealkylation reactions, the in-situ upgrading showed higher selectivity to xylenes and aromatics with nine carbons, and the ex-situ upgrading exhibited higher selectivity to benzene and toluene. A semi-batch lab-scale ablative pyrolysis reactor was designed and constructed to simulate the conditions that would be used in the mobile pyrolysis unit in the field. Prior to the ablative pyrolysis experiments, the wood temperature profile during reactor pre-heating was evaluated, and the modeling results suggested that the extent of slow pyrolysis of wood was insignificant, which is in good agreement with experimental measurements. In the ablative reactor, entire wood chips (up to 10 × 20 mm) were successfully pyrolyzed into bio-oil, of which yield was as high as 60 wt. % with a water content of 34%. The yield and composition of bio-oil from ablative pyrolysis were in the same range with those from fast pyrolysis of < 1 mm particles using a fluidized bed reactor, with the small differences (4 wt. % lower yield and HHV, and higher water content) attributed to the longer vapor residence times in ablative reactor. The effects of operating conditions on the ablative pyrolysis results were also investigated. The yield of bio-oil was favored at moderate pyrolysis temperature of 500 °C, thin layer of wood chips (≤ 5 mm), low applied pressure (≤ 0.5 bar), and high rotation speed (≥ 100 rpm). The elemental composition of bio-oil was highly affected by its water content, and the elemental composition of char was primarily affected by the temperature. At higher temperature, char became more carbonaceous in nature. Depending on the operating conditions, bio-oil and char had HHV of 11-15 MJ/kg and 28 MJ/kg, respectively.
Thesis (Ph.D.)--University of Washington, 2016-06
Keywords: Ablative pyrolysis; Beetle-killed trees; Bio-oil; Char; HZSM-5; Alternative energy; forestry